GYPSUM INVENTORY CONTROL USING ECONOMIC ORDER QUANTITY (EOQ) METHOD AT DEPO GYPSUM SUKOHARJO - Antariksa, Muhammad Ilham (Jurnal Ilmiah Mahasiswa FEB, 2016)
Inventory is an important component which supports the business activities of a company. The current era of global right competition right now requires companies to control inventory effectively and efficiently which can have an impact on customer satisfaction and loyalty. Depo Gypsum as one of the UKM in Sukoharjo has problems associated with gypsum inventory control. The Company has not had a clear standard in determining the order quantity of gypsum, furthermore the company does not have a minimum standard inventory quantity to reorder.The purpose of this study is to determine the raw material inventory control processes with the company's actual conditions and the effect of applying the EOQ method to the total cost of gypsum inventory. The data collection is conducted through observation and interviews directly to the company. Data collected were analyzed using the formula EOQ, ROP, order frequency, and Total Cost (TC).The results showed that by applying the EOQ, the company can determine the order quantity of gypsum is most economical. This study also provides a minimum standard inventory quantity gypsum to reorder through ROP.Key Words : Economic Order Quantity (EOQ), Order Quantity, Re-Order Point (ROP), Total Cost